Fazer-se elite em Santa Maria - RS: os imigrantes alemães entre estratégias políticas e sociais - 1830/1891 - Nicoloso, Fabrício Rigo (2013)
This work has for objective to comprehend the process of social and political insertion of german families in Santa Maria's society during the Empire and the first moments of Republic, covering a period about 60 years, since the first families of German immigrants had coming to Santa Maria around 1830, until the proclamation of the Constitution Riograndense July 14, 1891 . Through a dialog with the italian micro-history and utilising the metodology called prosopography, we will reconstruct the collective profile of 47 "germans" from Santa Maria's elite, belonging 16 local families, remaking the individual and collectives trajectories of some characters, in a vertical analysis, tracking their strategies for social inclusion, such as family ties and business, networks relationships, the economic activities that they developed and their performances in local politics. In this metodological exercise, we will elaborate a biographical questionnaire, with questions that will be apply in a standardized way for the documentation and bibliography about one each of characters from delimited group, constituting the database to guide our analysis.